ผลของการเสริมสร้างพลังอำนาจต่อความสามารถในการดูแลของผู้ดูแลผู้ป่วยบาดเจ็บสมอง - เพ็ญนภา จายวรรณ์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Traumatic brain injuries impairs the self-care ability of patients resulting in the need for support and care by caregivers. In order to meet the needs of patients, promoting care ability among caregivers is essential for health care providers. This quasi-experimental study aimed to examine the effect of an empowerment process on caring capabilities of caregivers of patients with traumatic brain injury. The study participants composed of 52 family caregivers of admitted patients with traumatic brain injury in the neurosurgical ward of Chiangrai Pachanukroh Hospital during April to July 2014. The participants were divided into two groups: the first 26 participants received routine care while other 26 participants were assigned as the experimental group. The researcher provided training to individual participants in the experimental group according to the empowerment program developed by the researcher. Instruments for data collection included demographic record form and the Capability of Caregiver Assessment Questionnaire. The data were analyzed using 2-way repeated measured analysis of variance, and independent t-test. Results of the study revealed that: 1. Caregivers in the experimental group had a statistically significant (p<.001) higher rate of appropriate care practices for patients with traumatic brain injury than those who received routine care as measured on the discharge day and 1 month after discharge from the hospital. 2. Caregivers in the experimental group had a statistically significant higher rate of appropriate care practices for patients with traumatic brain injury (p<.05) on the discharge day and 1 month after discharge from the hospital when compared with care practices measured before entering the study. There was no significant difference in care practices between the discharge day and 1 month after discharge. Study findings can contribute to nursing service in terms of improving capabilities among family caregivers of patients with traumatic brain injury. Further research is recommended and a longer follow-up period is needed to ensure the sustainability of the care capabilities among caregivers.